Perencanaan Ruang Berbasis Kemampuan Lahan di Sub Das Brantas Hulu - Pusparini, Nadia; Bisri, Mohammad; Ernawati, Jenny (Jurnal Tata Kota dan Daerah, 2012)
Critical Watershed in the Brantas Hulu, is constantly increasing. Its impact on the environment are various disasters and critical conditions such as erosion, flooding, landslides, until the loss of spring water sources, drought and land-use changes. It is necessary to plan the space in an area for the function of preservation area and development area. Analisys methods that had used are analyzing of erotion danger level (TBE), the determination of critical lands analysis with scoring techniques, analysis of land capability class classification with map overlay techniques, and analysis of existing land use suitability with land capability with matching methods. The results of this analysis show that the 4813,34 hectares or 27,75 % of the Sub DAS Brantas Hulu is a critical area. While the ability of land shows that the Sub DAS Brantas Hulu is on land capability class III to class VIII, is dominated by class VII (44,91%). The use of existing land in Sub Watershed Brantas Hulu that is not categorized according to the ability of the land area is 9984,89 ha (57,57 %). Spatial planning based on land capabilities in the Sub DAS Brantas Hulu is 2916,65 ha of preservation area, 964,54 ha of forest plantation, 399,53 ha of reforestation, 8724,32 ha of agroforestry ,1856,85 ha of settlement area, 606,66 ha of plantation, 824,92 ha of fields, and 710,14 ha of agricultural land.Keywords : DAS, Critical Lands, Land Capability